2012
DOI: 10.1017/s0267190512000025
|View full text |Cite
|
Sign up to set email alerts
|

Formulaic Language and Second Language Acquisition: Zipf and the Phrasal Teddy Bear

Abstract: This article revisits earlier proposals that language learning is, in essence, the learning of formulaic sequences and their interpretations; that this occurs at all levels of granularity from large to small; and that the language system emerges from the statistical abstraction of patterns latent within and across form and function in language usage. It considers recent research in individual differences, the psycholinguistics of language processing, and longitudinal studies of first (L1) and second (L2) langu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
142
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(154 citation statements)
references
References 105 publications
8
142
0
4
Order By: Relevance
“…Importantly, however, this does not mean that L2 learners do not use chunking processes (both top-down and bottom-up) in their development of the L2 (Ellis, 1996(Ellis, , 2003(Ellis, , 2012, as the next section will demonstrate. It is not because many externally defined FSs do not seem to have psycholinguistic reality in L2 learners that they do not use FSs: Their store of FSs needs to be investigated in its own right, that is by investigating which sequences present a processing advantage for L2 learners.…”
Section: Speaker-external Approaches To Formulaicitymentioning
confidence: 97%
See 2 more Smart Citations
“…Importantly, however, this does not mean that L2 learners do not use chunking processes (both top-down and bottom-up) in their development of the L2 (Ellis, 1996(Ellis, , 2003(Ellis, , 2012, as the next section will demonstrate. It is not because many externally defined FSs do not seem to have psycholinguistic reality in L2 learners that they do not use FSs: Their store of FSs needs to be investigated in its own right, that is by investigating which sequences present a processing advantage for L2 learners.…”
Section: Speaker-external Approaches To Formulaicitymentioning
confidence: 97%
“…Moreover, the construct of an FS as a processing (rather than lexical) unit fits better with the notion of formulaicity as a graded phenomenon, with linguistic knowledge viewed as a formulaic-creative continuum (Ellis, 2012).…”
Section: Speaker-internal Approach To Formulaicitymentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, FS plays a dual role of cognitive dimension and rapid means of access to whole chunks. In the recent study, the importance of learning formulaic sequences was acknowledged (Ellis, 2008(Ellis, , 2012Ellis & Larsen-Freeman, 2009;Myles & Cordier, 2017). Eskildsen (2012) reported that the frequency of FS English negation patterns among Spanish adult learners demonstrated an effect on English learning.…”
Section: Formulaic Sequencesmentioning
confidence: 99%
“…In this sense, it is also effective in second language acquisition (Ellis, Simpson-Vilach & Maynard, 2008;Ellis, 2012;Wood, 2002;Wray, 2000).…”
Section: Formulaic Language In Language Teachingmentioning
confidence: 99%